2019
DOI: 10.1039/c8ra10319d
|View full text |Cite
|
Sign up to set email alerts
|

Study of the perpendicular self-assembly of a novel high-χ block copolymer without any neutral layer on a silicon substrate

Abstract: A novel type of high-χ block copolymer, polystyrene-block-polycarbonate (PS-b-PC), which contains an active –NH– group on the polymer backbone between the PS block and the PC block, has been successfully synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In general, lithography requires BCPs with a high χ parameter, high etching contrast, and orientation control. 1,2 Among all reported BCP materials, silicon-based ones are advantageous due to their high χ parameter and etching contrast. The high χ parameter enables minimization of both the self-assembled periodic nanostructure and the interfacial roughness.…”
Section: Introductionmentioning
confidence: 99%
“…In general, lithography requires BCPs with a high χ parameter, high etching contrast, and orientation control. 1,2 Among all reported BCP materials, silicon-based ones are advantageous due to their high χ parameter and etching contrast. The high χ parameter enables minimization of both the self-assembled periodic nanostructure and the interfacial roughness.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, a new material polystyrene-b-polycarbonate (PS-b-PC) is used, which not only has a small molecular weight, but also has a high χ value of 0.19. [42] It is shown that by mixing PS-b-PC with PS, the phase state is changed from lammella to cylinder and the pitch is ≈24 nm. [43] However, in this work, it is found that such cylinder phase state is no longer a time-stable state.…”
Section: Introductionmentioning
confidence: 99%